2020
DOI: 10.1039/d0dt02364g
|View full text |Cite
|
Sign up to set email alerts
|

Smart dual T1 MRI-optical imaging agent based on a rhodamine appended Fe(iii)-catecholate complex

Abstract: The high spin Fe(iii) complex Fe(RhoCat)3 is reported as a smart dual-modal T1 MRI-optical imaging probe to visualize the NO molecule and an acidic pH environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…For example, a recent study shows the formation of dimeric μ-hydroxy Fe­(III) complexes in solution that have reduced r 1 relaxivity . Other examples of Fe­(III) agents require the addition of cosolvents to solubilize the complexes for solution studies or have low stability under physiological conditions including neutral pH. …”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent study shows the formation of dimeric μ-hydroxy Fe­(III) complexes in solution that have reduced r 1 relaxivity . Other examples of Fe­(III) agents require the addition of cosolvents to solubilize the complexes for solution studies or have low stability under physiological conditions including neutral pH. …”
Section: Introductionmentioning
confidence: 99%
“…44,45 Very recently, a system based on a Fe(III) ion coordinated to three catecholate ligands bearing a rhodamine moiety on their surface was reported to display, through the binding to HSA, relaxometric enhancement properties similar to the ones herein reported for Fe(DFX) 2 . 46 As mentioned above, the assignment of the observed relaxation enhancement for Fe(DFX) 2 in serum to the closest protons on second sphere water molecules may represent an oversimplification as likely other mobile protons on the protein in the proximity of the interaction site may contribute. The involved protons (whatever is their origin) are in fast exchange with the bulk solvent as demonstrated by the decrease of the observed relaxivity upon the increase of the temperature.…”
Section: ■ Discussionmentioning
confidence: 96%
“…It follows that the reorientational motion of the second sphere water molecules becomes relevant to determine the relaxivity enhancement when the magnetic field strength is increased. The exploitation of the lengthening of T 1e was a common practice in the case of slowly moving GBCAs displaying relaxivity peaks at around 1 T where the correlation times for the electronic relaxation of Gd­(III) ions approach the value of the molecular reorientational time (for HSA bound complexes, τ R is the range of 3–20 ns). , Very recently, a system based on a Fe­(III) ion coordinated to three catecholate ligands bearing a rhodamine moiety on their surface was reported to display, through the binding to HSA, relaxometric enhancement properties similar to the ones herein reported for Fe­(DFX) 2 …”
Section: Discussionmentioning
confidence: 99%
“…The large relaxivities in human serum were then attributed to the water molecules in the second coordination sphere. The binding capacity of the complex to HSA was studied in detail by the titration experiments with different concentration of the complex or HSA [ 43 ]. The results indicated that three Fe(III)–(DFX) 2 units bind tightly to one molecule of HSA with an average apparent binding constant ( K a) of 2.8 × 10 5 M −1 .…”
Section: Mononuclear Fe(iii) Complexesmentioning
confidence: 99%